Microfinance and social upliftment – An empirical investigation in Gujarat - Abda, Sachin (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Microfinance is provision of financial services to poor who finds it difficult to get financial facilities from formal financial institutions. By providing financial facilities to poor at reasonable rates it provides poor employment opportunities and opportunity to increase their incomes and savings. Directly it uplifts poor economically. Economic development and social status are inter- connected as economic growth affects quality of life and social status of an individual. The present study is an attempt to evaluate impact of microfinance on social status of beneficiary. For study data were collected from rural beneficiaries of Microfinance. The study presents significant positive impact of microfinance on social status of beneficiaries.